A new distributional record of the black coral Antipathes cf. griggi in Mactan Island, Philippines - Bacharo, Kurt Bryant B.; Sotto, Filipina B. (Zootaxa, 2020)
The black coral Antipathes cf. griggi was reported for the first time outside the Hawaiian Archipelago. This short report provides details and short description of the newly recorded species in Mactan Island, Philippines.